Lego mindstorm - Fu, Anqi. (2013)
In the time when natural disaster happened, a robot can be sent to explore a closed environment, such as collapsed houses, before sending an actual person in. This project focuses on the development of such robot explorer. The robot supports two operating modes: movements controlled by user through user interface; movement initiated by the NXT robot by listening to sound sources. To establish a successful connection between the robot and PC, Bluetooth is used to parse commands to the robot. To implement the project, a Lego Mindstorms kit and leJOS NXJ are used as the hardware and the programming language. The relationship between sound sensor output and sound location were analyzed with supporting data.